Aplikasi Bioleaching Dalam Pemisahan Logam Nikel Oksida dengan Jamur Aspergillus niger dan Penicillium chrysogenum - Rony Kurniawan (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2018)
Nickel ore processing plant in Indonesia is currently done by pyrometalurgy. Processing in this way requires an expensive operating costs and the waste produced can have a negative impact on the environment and so we need an alternative technology that is more effective and efficient as well as environmentally friendly. One alternative technology of low-grade nickel ore processing is the bioleaching process. Bioleaching process is a process of dissolution or release of metal or retrieval (extraction) metals from minerals into a soluble form with the aid of microorganisms.Thisstudygenerallyaimstoseparatethenickelfromlow-gradenikelore (nickeloxide) in ionic form withbioleachingprocess,andspecificallyaimstodeterminethe effectofbioleachingtime(15,30,and60days), ), theratioofmasstovolumeofnickeloresolvent (0,1 g/150 mL; 0,3 g/150 mL; 0,5 g/150 mL) andtype ofmicrooganism used (Aspergillusniger and Penicillium chrysogenum) in bioleaching process based on the concentration and yield value of the metal ion (Ni) from the extraction and knows the effect of microorganisms on the selectivity of Ni metal extracted in bioleaching process from nickel oxide. Theparameterusedarebioleaching temperature (37˚C),volume ofmicroorganisms(20% ofthe totalvolume of work),andtheparticle sizeoftheoforenickel30/40mesh. From the results of this research, highest achievement of extracted nickel ion at the time of bioleaching for 60 days with Penicillium chrysogenum with the highest extractable nickel ion concentration 4,26 ppm by the ratio of raw material to solvent 0,3g/150 mL and  for the highest  % yield (mass nickel extracted raffinate of the mass of the ore is extracted) is 12,78% (gram/gram) by the ratio of raw material to solvent of 0.3 g / 150 mL.